The Correlation Between Students Emotion of Anxiety and Their Performance in English Class - Tauran, Stephanie Gloria Amanda; Kaparang, Sharon Natasya Erika (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Klabat, 2025)
This study investigates the relationship between student anxiety and academic performance, motivated by concerns that anxiety negatively affects classroom outcomes. Using a quantitative method, the research involved 42 participants and found that students generally experienced moderate anxiety, with an average score of 3.24 (ranging from 2.14 to 4.36). Similarly, students in class XI IPS 2, 3, and 4 demonstrated moderate academic achievement. A correlation analysis revealed a significant inverse relationship between anxiety levels and performance—students with higher anxiety tended to perform worse, while those with lower anxiety achieved better results. These findings highlight the impact of emotional well-being on academic success and suggest the importance of supporting students to manage anxiety effectively. Addressing this issue could lead to improved academic outcomes. The study also recommends that future research focus on developing and assessing interventions designed to reduce anxiety and enhance student performance in educational settings.